A revision of Vaccinium bullatum (Ericaceae): floral morphology, distribution and typification - Nuraliev, Maxim S.; Fritsch, Peter W.; Beer, Anton S.; Tong, Yihua; Averyanov, Leonid V.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P. (Phytotaxa, 2020)
A comprehensive morphological and taxonomic revision of Vaccinium bullatum, a species of Ericaceae from China and Vietnam, is presented. Typification of this species is performed and a specimen at P (P04022860) is designated as a second-step lectotype. The floral morphology of V. bullatum is described for the first time, based on the study of living plants in their natural habitat and dry collections. Sectional placement of the species is discussed in the light of new morphological data; its attribution to V. sect. Galeopetalum is partly corroborated. A full list of all available specimens examined, a distribution map, a drawing and colour photographs are included for the species.